Anticipated effects of burosumab treatment on long-term clinical sequelae in XLH: expert perspectives - Seefried, Lothar; Duplan, Martin Biosse; Briot, Karine; Collins, Michael T.; Evans, Rachel; Florenzano, Pablo; Hawkins, Neil; Javaid, Muhammad Kassim; Lachmann, Robin; Ward, Leanne M. (Frontiers in Endocrinology, 2023)
X-linked hypophosphatemia (XLH) is a rare, progressive, genetic disease with multisystem impact that typically begins to manifest in early childhood. Two treatment options exist: oral phosphate in combination with active vitamin D ("conventional therapy") and a fully human monoclonal anti-FGF23 antibody, burosumab. The clinical benefit of conventional therapy in adults is limited, and poor tolerance and complications are common. Burosumab was first approved as a treatment for XLH in 2018 and its disease-modifying benefits in clinical trials in children suggest burosumab treatment could also alter the disease course in adults. Without long-term clinical data on multiple XLH-related sequelae available, the results of an elicitation exercise are reported, in which eight global experts in XLH posited how long-term treatment with burosumab is anticipated to impact the life course of clinical sequelae in adults with XLH. Based on their clinical experiences, the available evidence and their disease understanding, the experts agreed that some long-term benefits of using burosumab are likely in adults with XLH even if they have a misaligned skeleton from childhood. Burosumab treatment is anticipated to reduce the incidence of fractures and halt the progression of clinical sequelae associated with conventional therapy. While the trajectories for established dental abscesses are not expected to improve with burosumab treatment, dental abscess development may be prevented. Starting treatment with burosumab in childhood to increase the likelihood of an aligned skeleton and continuation into and throughout adulthood to maintain euphosphatemia may optimize patient outcomes, although future real-world investigation is required to support this hypothesis.